Digitalization of Russian Economy within the Framework of the National Innovation Policy - IMAMOV, Marsel M.; SEMENIKHINA, Natalia B. (Journal of Advanced Research in Law and Economics, 2019)
National innovation policy is part of socio-economic policy and is focused on improving state regulation, development and stimulation of innovation. It is implemented using economic, regulatory and other mechanisms of state support. Digital economy affects the growth of the country's economy and the measurement of gross domestic product, productivity and sustainability of economic entities in all financial spheres. The purpose of the article is to analyze the national innovation policy in the regulatory aspect, as well as to analyze the state of development of science and innovation in the Russian Federation. In the process of research, the main method employed was a comparative analysis method, which allowed to achieve the purpose by means of a comprehensive research of the identified issue. To achieve the purpose, the following objectives were set: to consider the legal regulation of the innovation field in the Russian Federation; to evaluate the implemented and existing programs for the development of science and innovation in the Russian Federation. A review of legal documents allowed to conclude that they are of high importance for the development of the innovation field, since they constitute a systemic basis for the implementation of modernization processes and the qualitative improvement of the country's socio-economic development.